Dissecting a co-expression network of basic helix-loop-helix (bHLH) genes from phosphate (Pi)-starved soybean (Glycine max) - ÖZYİĞİT, İBRAHİM İLKER (Elsevier B.V., 2017)
In this work, a co-expression network-based approach was employed in analysis of basic helix-loop-helix (bHLH) transcription factor genes in soybean (Glycine max). bHLHs as regulatory agents modulate many complex associations related with regular metabolic functions and various stress factors. Co-expression networks are versatile resources to understand complex associations from functional aspects. Using a microarray data from phosphate (Pi)-starved soybean, a co-expression network of bHLH genes was constructed. A network was established with 253 nodes (bHLH genes) interconnecting 1763 edges (association) and then the network was dissected into 13 distinct clusters to extensively investigate the correlations. Each cluster was individually analyzed with emphasis on seed genes, which could be used as marker/reference genes in development of plant lines with enhanced stress tolerance. The seed genes were involved in very diverse metabolic processes, including stress modulation, metal homeostasis, hormone response and developmental roles. Our network-based clustering approach provides new insight in understanding many uncharacterized plant bHLHs. © 2016 Elsevier B.V.
Keywords: bHLH; Cis-element; Cluster; Co-expression; Gene module; Seed genes; Soybean